Early Detection of Checkpoint Inhibitor-Associated Myocarditis Using 68Ga-FAPI PET/CT - Finke, Daniel; Heckmann, Markus B.; Herpel, Esther; Katus, Hugo A.; Haberkorn, Uwe; Leuschner, Florian; Lehmann, Lorenz H. (Frontiers in Cardiovascular Medicine, 2021)
Objective Checkpoint inhibitors (ICIs) have gained importance in recent years regarding the treatment of a variety of oncologic diseases. The possibilities of diagnosing cardiac adverse autoimmune effects of ICIs are still limited. We aimed to implement FAPI PET/CT imaging in detecting ICI-induced myocarditis. Methods In a retrospective study, FAPI PET/CT scans of 26 patients who received ICIs from 01/2017 to 10/2019 were analyzed. We compared tracer enrichment in the heart of patients without any signs of a cardiac disease (n=23) to three patients with suspected ICI-induced myocarditis. To exclude any significant coronary heart disease, cardiac catherization was performed. All three patients’ myocardial biopsies were examined for inflammatory cells. Results Three patients showed clinical manifestations of an ICI syndrome including myocarditis with elevated levels of hsTnT (175 pg/ml, 1771 pg/ml, 157 pg/ml). Further cardiological assessments revealed ECG abnormalities, lymphocyte infiltration of the myocardium in the biopsies or wall motion abnormalities in echocardiography. These patients’ FAPI PET/CTs showed cardiac enrichment of the marker which was less distinct or absent in patients receiving ICIs without any signs of immunological adverse effects and cardiac impairment (n=23) (Median SUV myocarditis patients: 1.79 (IQR: 1.65, 1.85), median SUV non-myocarditis patients: 1.15 (IQR: 0.955, 1.52)). Conclusions Apart from the successful implementation of ICIs in oncological treatments, ICI-induced myocarditis is still a challenging adverse effect. FAPI PET/CT may be used in order to identify affected patients at an early stage. Moreover, when integrated into cancer stage diagnostics, it contributes to cardiac risk stratification besides biomarker, ECG and echocardiography.